ANALYSIS OF THE LEVELS OF DOING SPORT AND AGGRESSION IN HIGH SCHOOL STUDENTS - Acar, Hakan; Tutkun, Erkut; Yıldırım, Özgür Devrim; Çıplak, Mustafa Ertuğrul Çıplak (Acta Scientiae et Intellectus, 2024)
The objective of this study is to examine the aggression levels of high school students who do and who do not do sports and to examine the effects of sport on aggression levels. In this study, survey method was used to measure the aggression levels. Aggression inventory, which was developed by Kiper and which had 30 items, was used to measure aggression. 78 male students studying in a high school of Samsun were included in the study. 43 of these students were licensed athletes, while 35 did not do sports. As for statistical methods, descriptive statistics and independent t test were used, following normality tests. The data obtained were recorded in SPSS 20 program and significance level was accepted as p<0.05. When the destructive aggression, passive aggression and assertiveness levels of volleyball players and wrestlers were compared, no statistically significant difference was found (p>0.05). When athlete and non-athletes groups were compared, statistically significant difference was found (p<0.05). As a result, significant differences were found in destructive aggression, passive aggression and assertiveness of athletes when compared with non-athletes.